Elementary School Students' Perceptions On The Use Of The Savi Learning Model In Efforts To Improve Writing Skills - Kurniati, Eka; Gunarhadi, Gunarhadi; Yulisetiani, Septi (Jurnal Mamangan, 2023)
Writing is a language skill that needs to be taught seriously because it is related to creative thinking. However, it is inversely proportional to the current reality where learning to write is very less attractive to elementary school students, because it is still the application of a one-way learning model that makes students passive. Currently SDN Luworo 01 and SDN Luworo 03 Pilangkenceng have implemented learning innovations with the SAVI learning model. The purpose of this study is to determine the perceptions of students on the SAVI learning model and how it impacts students. This research is descriptive qualitative, using a survey approach. The research subjects were teachers and phase c learners of class V. Methods for collecting data include documentation, questionnaires, interviews, and observation. Participants totaled 40 people consisting of 2 teachers and 38 students. Data analysis was carried out interactively through the stages of: (a) Collecting data; (b) Data assessment; (c) Interpreting data; (d) Making data conclusions. The results showed that most of the fifth grade students gave positive responses/perceptions to the SAVI learning model and were considered interesting and able to improve students' writing skills. During learning, teachers are also considered capable and have sufficient insight when applying the SAVI learning model in class.